Anomaly Search in a Public Key Infrastructure OPENSSL v1.0 1e. - Castro Lechtaler, Antonio (2013)
Public key infrastructure is used in most networks requiring user authentication, digital signature, cryptographic confidentiality, and non repudiation of information. The main protocols and architectures used in a PKI are the public key cryptosystem and the RSA digital signature. Their robustness is based on the difficulty to obtain prime factors of a large composite number. Notwithstanding, if the primes generated by a PKI are predictable or represent a small set of possible primes, the security of the PKI certificate is compromised. This article is part of a line of research aiming to develop auditing tools of PKI performance and to detect anomalies in the generation and distribution of prime values delivered by OpenSSL, if such anomalies are present.